6(8n-1)+7=8(6n+8)

Simple and best practice solution for 6(8n-1)+7=8(6n+8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(8n-1)+7=8(6n+8) equation:


Simplifying
6(8n + -1) + 7 = 8(6n + 8)

Reorder the terms:
6(-1 + 8n) + 7 = 8(6n + 8)
(-1 * 6 + 8n * 6) + 7 = 8(6n + 8)
(-6 + 48n) + 7 = 8(6n + 8)

Reorder the terms:
-6 + 7 + 48n = 8(6n + 8)

Combine like terms: -6 + 7 = 1
1 + 48n = 8(6n + 8)

Reorder the terms:
1 + 48n = 8(8 + 6n)
1 + 48n = (8 * 8 + 6n * 8)
1 + 48n = (64 + 48n)

Add '-48n' to each side of the equation.
1 + 48n + -48n = 64 + 48n + -48n

Combine like terms: 48n + -48n = 0
1 + 0 = 64 + 48n + -48n
1 = 64 + 48n + -48n

Combine like terms: 48n + -48n = 0
1 = 64 + 0
1 = 64

Solving
1 = 64

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 3y-0.5=1.4y+3.1 | | 72x-9/2x^2 | | M/4=-4.1 | | 3x-8y+45=0 | | -x+47=3x+15 | | t/-8=16.2 | | 4x+3y=14-y | | 4/5×n=26 | | B-4.25=-16.5 | | 8x^2+22x-30=0 | | K+3.5=45 | | 73-4x=0 | | 3.5=4.7-0.6x | | 12-40x=76-13x | | 73x-43x=200 | | 56+x=40+5x | | 5/8x-10=0 | | 8/5x-5= | | 15x-10+10x= | | 12x-4=30x-120 | | T=0.3m^2-5.1m+9 | | 9(3x-4)=26x-3 | | 9(3x-4)=26(x-3) | | 2x+2y-27=0 | | 5x+4+3x-x+7=6x-8 | | X^2+0.11x-0.057=0 | | 13x=12x-1 | | 21x^2+14x-40=0 | | 7+x(7)=3 | | 2x-5yi=4+15i | | 4/16-15/25 | | 15-3t=17-t |

Equations solver categories